Impact of Value Added Tax to Enugu’s Economy - GONZALES, MARIA LUISA; ODE, FRIDAY (Advances in Social Sciences Research Journal, 2021)
ABSTRACT Value-added tax is everywhere; it is in the most of goods and services we purchase. Take for instance; when we go to the salon to get our hair done, when we gas up our car, vat is also included in what we pay. In the Philippines, the value-added tax is a form of sales tax. It is a tax on the consumption levied on the sale, barter exchange, or lease of goods, properties, and services in the Philippines, and on importation of goods into the country, it is an indirect tax that may be shifted or passed into the buyer transferring lease of goods, properties or services. While in Nigeria, VAT is a Federal Government Tax that is administered using the existing machinery of the Federal Inland Revenue Services (FIRS). This study assessed the impact of value-added tax on Enugu Nigeria’s Economy, specifically to Government, Business Organizations, and Consumers, the problems identified, significant relationships, and the solutions recommended. The findings revealed that VAT has a significant impact on business organizations and consumers but positively on the part of the government. Recommendation for the improvement is for the consumer with low average earnings should be exempted in paying the VAT provided however, criteria must be set to exempt them in VAT. Keyword: Social Sciences, Impact, Value added Tax, Revenue, descriptive research design, Philippines